Random Mutagenesis by Insertion of Error-Prone PCR Products to the Chromosome of Bacillus subtilis - Ye, Bin; Li, Yu; Tao, Qing; Yao, Xiaoliang; Cheng, Minggen; Yan, Xin (Frontiers in Microbiology, 2020)
Bacillus subtilis is an attractive host for directed evolution of the enzymes whose substrates cannot be transported across cell membrane. However, generation of mutant library in B. subtilis still suffers problems of small library size, plasmid instability and heterozygosity. Here, large library of random mutant was created through inserting error-prone PCR (epPCR) products to the chromosome of B. subtilis. Specifically, the epPCR product was fused with flanking regions and antibiotic resistant marker using a PCR-based multimerization method, generating insertion construct. The epPCR product was integrated into chromosome via homologous recombination after insertion construct was transformed into the supercompetent cells of B. subtilis strain SCK6. The transformation efficiency of insertion construct was improved through co-expressing homologous recombination-promoting protein NgAgo, raising the number of competent cells, and increasing the length of flanking regions. A library containing 5.31×105 random mutants was constructed using per μg insertion construct, which is sufficient for directed evolution. Moreover, the library generation process could be accomplished within one day. The effectiveness of this method was confirmed by improving the activity of Methyl Parathion Hydrolase (MPH) toward chlorpyrifos and by enhancing the secretion level of MPH in B. subtilis. Taken together, present work provides a fast and efficient method to integrate epPCR products into the chromosome of B. subtilis, facilitating directed evolution and expression optimization of target proteins.